Polemika Władysława Konopczyńskiego z Mieczysławem Skibińskim - Biliński, Piotr (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2015)
A famous polemic between Władysław Konopczyński and Mieczysław Skibiński took place in the interwar period in Cracow. Konopczyński in „Historical Quarterly” criticized Skibiński’s dissertation titled: Europe and Poland in the era of the War for the Austrian Succession in the years 1740–1745. After closing the polemic by the editors, the dispute between historians moved to the meetings of the Krakow branch of Polish Historical Society, Historical Commission of the Polish Academy of Sciences and the Faculty of Philosophy of the Jagiellonian University. After years Konopczyński prevented Skibiński from carrying out his habilitation process at the Jagiellonian University, which brought about his mental breakdown. After the Second World War, the conflict finally expired.